Implementation and development of knowledge management system – research results. - Tabaszewska, Edyta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
The objective of the paper is to present the results of professional literature and empirical studies referring to both implementation and development of knowledge management system (KMS) by focusing on existing conditions. The additional objective is also to present methods of effectiveness measurements applied by studied enterprises. Two types of enterprises were analyzed: manufacturing and knowledge offering enterprises, which facilitated the identification of differences and similarities in the studied domain. The leading research objective was to define guidelines regarding methodology for introducing a knowledge management system, that resulted in not exclusively cognitive but also utilitarian orientation of the study
Argumenta Oeconomica, 2011, Nr 1 (26), s. 111-148
Keywords: knowledge management; knowledge management system; implementation; information management; human resources management; zarządzanie wiedzą; systemy zarządzania wiedzą; zarządzanie informacją; zarządzanie zasobami ludzkimi